Response of Afromontane soil organic carbon, nitrogen, and phosphorus to in situ experimental warming along an elevational gradient - Okello, Joseph; Bauters, Marijn; Verbeeck, Hans; Kasenene, John; Boeckx, Pascal (Frontiers in Soil Science, 2022)
Tropical montane forests store large amounts of carbon (C), nitrogen (N) and phosphorus (P) in soil. These soil C, N and P pools are vulnerable to increased losses due to the increasing local temperatures. To gain better insight into the effects of climate warming on biogeochemistry in montane forests in Africa, we established study plots along a natural climate gradient in Uganda between 1250-3000 m in the Rwenzori Mountains. We studied soil C, N and P contents as well as 13C and 15N isotopic compositions and leaf nutrient contents. Further, we simulated climate warming by 0.9-2.8 °C for two years by conducting in situ soil mesocosms translocation down-slope. The results revealed that, along the elevational gradient, soil organic C increased six-fold from 2.6 ± 1.0 % at 1250-1300 m to 16.0 ± 1.9 % at 2700-3000 m, with a linear increase of 0.94 % per 100 m of elevation increase. Similarly, soil total N increased five-fold, from 0.3 ± 0.1 % to 1.3 ± 0.1 %, with a linear increase of 0.07 % per 100 m of elevation increase. Further, soil bio-available P increased three-fold, from 9.6 ± 5.2 mg kg-1 to 29.5 ± 3.0 mg kg-1, with a linear increase of 1.4 mg kg-1 per 100 m of elevation increase. Soil 15N decreased linearly by 0.39 ‰ per 100 m of elevation increase, ranging from 8.9 ± 0.2 ‰ to 2.9 ± 0.7 ‰ at 1250-1300 m and 2700-3000 m respectively. The accumulation of soil organic C and total N with elevation is due to slow microbial activity under lower temperature. Indeed the soil 15N indicated a more closed N cycling with increasing elevation. However, despite the increasing trend in soil C and nutrient status with elevation, leaf N and P contents decreased linearly with elevation. This is likely due to the impairment of nutrient uptake under low temperature and low pH. In addition, following two years of in situ soil warming, we found that the soil δ13C and δ15N values relatively increased. Generally, the results imply that warming triggered accelerated transformation processes of accrued soil organic matter.